Pengaruh solvabilitas dan likuiditas terhadap profitabilitas pada perusahaan perbankan yang terdaftar di Bursa Efek Indonesia (BEI) - Husniar, Husniar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of solvency and liquidity on profitability in banking companies listed on the Indonesia Stock Exchange. This study is a quantitative study using secondary data in the form of financial statements of banking companies listed on the Indonesia Stock Exchange for the period 2018-2020. The independent variables used in this study are solvency (X1), liquidity (X2) and while the dependent variable is profitability (Y). Determination of the sample in this study using purposive sampling. Data analysis used descriptive analysis test and multiple linear regression. The results showed that partially and simultaneously solvency and liquidity had no significant effect on the profitability of banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period.